Historia de Inglaterra / E. L. Woodward ; [traductor, Eugenio Gallego] - Gallego, Eugenio; Woodward, E.L. (El Libro de bolsillo Sección humanidades; 530)
1° ed. y reimp. de 1988, 1994 y 1996, 3° ed. 1984